Dynamic trait-niche relationships shape niche partitioning across habitat transformation gradients - Emilio Pagani-Núñez; Dan Liang; Chao He; Yang Liu; Xu Luo; Eben Goodale (Basic and Applied Ecology, 2022)
Multidimensional approaches examining complex trait-niche relationships are crucial to understand community assembly. This is particularly important across habitat transformation gradients because specialists are progressively substituted by generalists and, despite increasing functional homogenization, in both specialist and generalist communities niche partitioning is apparent. Here, in line with the continuum hypothesis, we expected that divergent trait-niche relationships would arise in passerine assemblages across the natural-to-urban transformation gradient. More specifically, we expected that traits linking form to function would be more important in less transformed habitats, while population density and traits linked to dispersal and dominance would predominate in more transformed habitats. Accordingly, we found that beak length and its interaction with tarsus length correlated significantly with isotopic niches in natural and rural habitats, where specialists predominate. Conversely, body size and aggressiveness only showed significant relationships with isotopic niches with increasing habitat transformation, where generalists prevail. Interestingly, we recorded a mix of these processes in rural habitats, which acted as a frontier between these two domains. Our study is thus important in showing that a complex combination of morphological and behavioral traits determine niche characteristics, and that these relationships are dynamic across habitat transformation gradients.